Genetic analysis: therapeutic drug monitoring of metformin and glimepiride on diabetic patients' plasma including genetic polymorphism - Areen Ibrahim; Mohanad Odeh; Eyad Mallah; Luay Abu-Qatouseh; Ahmad Abu Awaad; Mohammad I. A. Ahmad; Amjad Shdifat; Soadad Saleh; Muwafaq Al Hyari; Ibrahim Khadra; Khaled W. Omari; Tawfiq Arafat (Wolters Kluwer Medknow Publications, 2024)
Diabetes is a widespread disease that needs to be controlled. Therapeutic monitoring of drugs is very helpful in maintaining desirable doses. To study a correlation between the blood level of metformin (to a lesser extent, glimepiride) and genotyping (mainly the SULT1A1 genotype). Determine drug levels using a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) tool. A validated LC-MS/MS method was developed to determine metformin and glimepiride levels in human plasma. DNA extraction was performed using Jena Bioscience's Blood DNA preparation, in which a column kit was used to extract DNA for genetic polymorphism. The investigation was carried out using both medications in type 2 diabetes patients alongside the genetic polymorphism. One hundred and six patients were assessed. The prevalence of homozygosity for SULT1A1 and wild-type CYP2D6 * 4 were 72.6% and 73.6%, respectively. After adjustment for daily intake of metformin, three patients out of five with the highest levels of metformin had no homozygosity (SULT1A1 genotype). Statistically, variables that demonstrated an insignificant correlation with the level of metformin were body mass index (rs (87) = 0.32, P = 0.011) and age (rs (87) =0.26, P = 0.017). The homozygous (SULT1A1 genotype) correlation was moderate (rs (87) =0.21, P = 0.052). According to the findings, patients with the wt/wt CYP2D6 genotype had considerably greater levels of endoxifen than those with the v/v CYP2D6 genotype. The study's results reported a probable correlation between the blood level of metformin (to a lesser extent, glimepiride) and genotyping (mainly the SULT1A1 genotype). Genotype-guided drug therapy may provide a novel contribution to maximize drug efficacy and/or minimize toxicity.